The Influence of Foreign Direct Investment, Portfolio Investment, Remittance Receipts, Exchange Rates on Economic Growth in 10 APEC Countries - Febriani, Nesa; Armaya, Armaya; Refinika, Meidi; Putra, Agung Rizki (Trunojoyo University of Madura, 2024)
Every country has problems and challenges related to the influence of factors that influence economic growth. Many things influence the economic growth of a country. This research aims to determine the effect of foreign direct investment, portfolio investment, remittance receipts, exchange rates on the economic growth of 10 APEC countries (Australia, Canada, China, Chile, Japan, Malaysia, Mexico, New Zealand, the Philippines and Russia). This research method uses panel data regression analysis. The results of this research show that partially foreign direct investment (x1) has a positif and significant effect on the economic growth of 10 APEC countries. Portfolio investment (x2) has a negative and insignificant effect on the economic growth of 10 APEC countries. Remittance receipts (x3) have a negative and insignificant effect on the economic growth of 10 APEC countries. The exchange rate (x4) has a negative and insignificant effect on the economic growth of 10 APEC countries. In conclusion, this research shows that of the four variables studied, only the foreign direct investment has a significant positive influence on the economic growth of 10 APEC countries. Other variables, such as portfolio investment, remittance receipts, and excange rates do not show a significant influence on the economic growth of these countries.